2005
DOI: 10.1152/ajprenal.00061.2005
|View full text |Cite
|
Sign up to set email alerts
|

COX-2 inhibition prevents downregulation of key renal water and sodium transport proteins in response to bilateral ureteral obstruction

Abstract: Bilateral ureteral obstruction (BUO) is associated with marked changes in the expression of renal aquaporins (AQPs) and sodium transport proteins. To examine the role of prostaglandin in this response, we investigated whether 24-h BUO changed the expression of cyclooxygenases (COX-1 and -2) in the kidney and tested the effect of the selective COX-2 inhibitor parecoxib (5 mg.kg(-1).day(-1) via osmotic minipumps) on AQPs and sodium transport. Sham and BUO kidneys were analyzed by semiquantitative immunoblotting,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
99
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(127 citation statements)
references
References 52 publications
26
99
2
Order By: Relevance
“…Immunohistochemistry confirmed an up-regulation of COX-2 in the obstructed kidneys. This is consistent with previous reports demonstrating an increase COX-2 expression in response to BUO, 12 in response to occlusion of a solitary kidney, 11 and also in kidney inner medullary (IM) of rats subjected to UUO. 10 Neonatally-induced ureteral obstruction results in severe injury of the obstructed kidney.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Immunohistochemistry confirmed an up-regulation of COX-2 in the obstructed kidneys. This is consistent with previous reports demonstrating an increase COX-2 expression in response to BUO, 12 in response to occlusion of a solitary kidney, 11 and also in kidney inner medullary (IM) of rats subjected to UUO. 10 Neonatally-induced ureteral obstruction results in severe injury of the obstructed kidney.…”
Section: Discussionsupporting
confidence: 93%
“…11 Moreover, it was recently demonstrated that acute BUO leads to marked upregulation of COX-2 in inner medulla; selective COX-2 inhibition prevents dysregulation of AQP2 in response to BUO, indicating that COX-2 may be an important factor contributing to the impaired renal water and sodium handling in response to BUO. 12 Thus, it is speculated that impaired renal water handling in response to neonatally-induced PUUO may be associated with altered expression of COX-2. In the present study, we examine whether long-term PUUO induced at birth affects the abundance of renal cyclooxygenase.…”
Section: Introductionmentioning
confidence: 99%
“…The COX-2 upregulation in the kidney is presumably regulated by inhibition of glyet al, 2004, 2005) or possibly other kinases (Li and Matsumura, 2008;Dong and Matsumura, 2008). The elevation of PGE 2 will suppress the expression of AQP2 (Norregaard et al, 2005) membrane of the collecting duct epithelium (Nejsum et al, 2005), which subsequently suppresses the water permeability and leads to polyuria (Rao et al, 2005;Kim et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…During this period, intraurethral pressure is above normal range and intrarenal blood-flow is redistributed from medullar to cortex (13). These events under BUO conditions can increase renal vascular resistance and then, reduce GFR (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…In OU, the initial event is vasodilatation, which lasts 90 minutes; then, more prominent drops occur in renal blood flow, that maybe attributed to release of strong vasoconstrictors, angiotensin II, and thromboxane A2 (7,11,13). During this period, intraurethral pressure is above normal range and intrarenal blood-flow is redistributed from medullar to cortex (13).…”
Section: Discussionmentioning
confidence: 99%